Asymptotic speeds of spread and traveling wave solutions of a second order integrodifference equation without monotonicity. Issue 4 (2nd April 2016) - Lin, Guo; Su, Ting
Abstract : This paper is concerned with the propagation modes of a second order integrodifference equation without monotonicity. The equation cannot generate monotone semifolws. By constructing auxiliary functions/equations and applying some known results, the minimal wave speed of traveling wave solutions and asymptotic speeds of spread are established.